2021
DOI: 10.15295/bmij.v9i1.1757
|View full text |Cite
|
Sign up to set email alerts
|

Pandemi sürecinde üniversite öğrencilerinin psikolojik dayanıklılıkları ve umutsuzluklarının kariyer geleceği algısı üzerindeki etkileri

Abstract: İş piyasasına giriş öncesinde, bireylerin kendilerini tanıması, niteliklerini değerlendirmesi, çevresindeki fırsatların farkına varması ve bunlardan yararlanarak kariyer hedeflerini belirlemesi son derece önem arz etmektedir. Fakat kariyer planlama sürecinde yaşanan olumsuz olaylar ve krizler bu süreci önemli derecede etkilemektedir. Yaşanan (Covid-19) pandemi süreci, üniversite öğrencilerinin kariyer planlaması açısından önemli bir kriz durumu yaratmıştır. Bu araştırmanın amacı, pandemi sürecinde üniversite ö… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 18 publications
1
3
0
2
Order By: Relevance
“…Since no previous study examining the career barriers and psychological resilience levels of university students together could be found in the literature, the research results indirectly related to those of this study were examined. Srivastava and Madan (2020) stated that career satisfaction is positively related to the level o f X X resilience; Alnıaçık et al (2021) and Bimrose and Hearne (2012) reported that psychological resilience was positively related to the perception of career future, and Shin and Kelly (2015) found that psychological resilience is an important variable for coping with career decision-making difficulties. It can therefore be said that the results of those studies indirectly support the results obtained in the current study.…”
Section: A Discussion Of the Findings Related To The Levels Of Career...mentioning
confidence: 99%
See 1 more Smart Citation
“…Since no previous study examining the career barriers and psychological resilience levels of university students together could be found in the literature, the research results indirectly related to those of this study were examined. Srivastava and Madan (2020) stated that career satisfaction is positively related to the level o f X X resilience; Alnıaçık et al (2021) and Bimrose and Hearne (2012) reported that psychological resilience was positively related to the perception of career future, and Shin and Kelly (2015) found that psychological resilience is an important variable for coping with career decision-making difficulties. It can therefore be said that the results of those studies indirectly support the results obtained in the current study.…”
Section: A Discussion Of the Findings Related To The Levels Of Career...mentioning
confidence: 99%
“…This means that as their career barriers increased, their level of perception of the future also increased. Cetin et al (2015) repoprted that individuals who could plan their future showed higher psychological resilience and Alnıaçık et al (2021) similarly found a significantly positive relationship between individuals' career future perception and their psychological resilience levels. It can therefore be said that the results of those studies are similar to the findings obtained in the current study and support this finding.…”
Section: A Discussion Of the Findings On The Sub-dimensions Of The Pa...mentioning
confidence: 99%
“…The fear and uncertainty that pandemic conditions created increased anxiety and worries in the workforce about their future career (Wang et al, 2020). On the contrary, psychologically resilient and hopeful individuals' are more skillful in career adaptability and career optimism in the case of future career plans (Keleş and Özkan, 2016;Özkan, 2017;Alnıaçık et al, 2021). Besides, psychological resilience is highly correlated with self-efficacy and active coping (Rees et al, 2015).…”
Section: The Covid-19 Pandemic Vs Individual/ Personal Factorsmentioning
confidence: 99%
“…Yaptıkları çalışmalarında da bu yönde bulgular elde edilmiş, salgın sürecinde üniversite öğrencilerinin uzaktan eğitimde karşı yaratıcılık ve yenilikçilik özellikleri noktasında düşüşün olduğu saptanmıştır (Örücü, Hasırcı ve Kurt, 2022). Alnıaçık, Of, Balkaş, Tülemez, Mirzayev ve Alfarra (2021) pandemi sürecinde üniversite öğrencilerinin psikolojik dayanıklılıkları ve umutsuzluklarının kariyer geleceği algısı üzerindeki etkileri adlı çalışmalarında üniversite öğrencilerinin psikolojik olarak dayanıklılıkları üzerinde durmuşlardır. Sosyal bir hayata sahip olan üniversite öğrencilerinin kısıtlılık durumundan kaynaklı olarak psikolojik sorunlar yaşadığı ve arkadaş ortamlarından uzak durdukları için buna negatif yönde tepki verdikleri anlaşılmıştır (Alnıaçık vd, 2021).…”
Section: Covid 19 Sürecinde Algılanan Stresin Motivasyon Ve Iş Bağlıl...unclassified